2014
DOI: 10.20965/jdr.2014.p0216
|View full text |Cite
|
Sign up to set email alerts
|

Practice on an Education and Training Program to Development of Response Literacy to Earthquake Disaster in a Central Business District in Japan

Abstract: This paper discusses an experiential training and education program designed to improve the response literacy in the event of a large-scale earthquake in the Shinjuku station area in Tokyo, which is a central business district representative of Japan. The features of the Shinjuku station area are described, and the activities of the Shinjuku Station Area Disaster Response Measure Committee, made up of businesses and other concerns located in the vicinity of Shinjuku station, as well as the education and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Hub is a base which collects various things. In Japan, while the training results for disaster responses have been evaluated on an individual basis (e.g., Takemoto et al (2010) [4], Masuzawa et al (2014) [5]), systematic research on disaster management literacy has not been conducted. Therefore, Kimura et al (2014) extracted the required capability for those involved in disaster responses in administrative offices or other organizations by analyzing "ICS All-Hazard Core Competencies" in the documents of the Federal Emergency Management Agency of the United States (FEMA) [6] Hub that would include a learning program for a life recovery support system using a victim ledger [7].…”
Section: Conceptual Design Of the Disaster Management Literacy Hub Anmentioning
confidence: 99%
“…Hub is a base which collects various things. In Japan, while the training results for disaster responses have been evaluated on an individual basis (e.g., Takemoto et al (2010) [4], Masuzawa et al (2014) [5]), systematic research on disaster management literacy has not been conducted. Therefore, Kimura et al (2014) extracted the required capability for those involved in disaster responses in administrative offices or other organizations by analyzing "ICS All-Hazard Core Competencies" in the documents of the Federal Emergency Management Agency of the United States (FEMA) [6] Hub that would include a learning program for a life recovery support system using a victim ledger [7].…”
Section: Conceptual Design Of the Disaster Management Literacy Hub Anmentioning
confidence: 99%
“…Each component was windowed in 20 s steps with a 5% cosine taper. Smoothing was performed to refine the pattern by using the Konno-Ohmachi method [24,25] and obtaining the HVSR with the logarithmic window function. The parameter results were relatively uniform at all sites: frequency of 1-5.5 Hz, period of 0-1 s, amplification of 0-1.8, and vulnerability of 0-2.4.…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted by Masuzawa et al [16] showed experimental research in the Shinjuku station area. The study began with seminars and workshops to comprehensively train employees on disaster preparedness and ended with a questionnaire consisting of five rating scales indicating participants' degrees.…”
Section: Resultsmentioning
confidence: 99%